Социальная реабилитация: учеб. пособие / Е. И. Холостова, Н. Ф. Дементьева - Холостова Евдокия Ивановна (Дашков и К°, 2004)
Экземпляры: КХ (20051121) / Инвентарный номер: 1054343 / Цена: 102.00 / Сис.шифр: 60.9 / Авт.знак: Х 73 / ГРНТИ: 04 / ББК: 60.99